2018
DOI: 10.18203/2320-1770.ijrcog20183426
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and breast-feeding practices of postnatal mothers in Central India

Abstract: Background: Breast feeding is vital for the health of baby & mother. It is of advantage to baby, mother, family, society and nation. Present study was carried out to evaluate knowledge, attitude and breast feeding practices of postnatal women.Methods: This cross-sectional study was carried out at immunization centre. 208 postnatal women were interviewed.Results: Out of 208 postnatal women, 148 women (71.15%) had delivery by caesarean section while 60 women (28.84%) had vaginal delivery. 118 women (56.73%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…8 Mothers intend to Wean infants after 6 months is 62.9% whereas 21.2% wants to wean their infants after 3 months in our study. Whereas weaning is 86.5% after 6 months and 13.5% after 3 months in Upadhye JV et al 9 There is a estimation of 1.4million deaths and 10% of the disease burden in less than 5 years of age is found in children with sub optimal breast feeding and exclusive breast feeding less than 6 months of age. 10 Lumbigaon P et al, showed that breast feeding education and counseling in antenatal mothers increases both exclusive breast feeding and duration of breast feeding among mothers post natally.…”
Section: Resultsmentioning
confidence: 97%
“…8 Mothers intend to Wean infants after 6 months is 62.9% whereas 21.2% wants to wean their infants after 3 months in our study. Whereas weaning is 86.5% after 6 months and 13.5% after 3 months in Upadhye JV et al 9 There is a estimation of 1.4million deaths and 10% of the disease burden in less than 5 years of age is found in children with sub optimal breast feeding and exclusive breast feeding less than 6 months of age. 10 Lumbigaon P et al, showed that breast feeding education and counseling in antenatal mothers increases both exclusive breast feeding and duration of breast feeding among mothers post natally.…”
Section: Resultsmentioning
confidence: 97%
“…Range was from 72.9% in Kerala, 17.5% in Rajasthan and 17.3% in Uttarpradesh. In all major states in Kerala urban 72.9% and rural69.3% Tamil nadu urban 55.4% and rural 56.5%, Andrapradesh urban 59.4% and rural 47.8%, Himachal Pradesh urban 61.3% and rural 39.9% and Delhi urban37.0% and rural 25.1% more than 50% of infants of age 6to9 months were not receiving semisolid food in other states (Upadhye et al, 2018). (Singh et al, 2006) conducted a study on "Infant feeding and weaning practices" in semi-arid rural areas of Rajasthan.…”
Section: Introductionmentioning
confidence: 96%